Divide and Conquer: The Initiation and Proliferation of Meristems. (4th March 2021) - Schwartz, Michael F.; Peters, Rachel; Hunt, Aitch M.; Abdul-Matin, Abdul-Khaliq; Van den Broeck, Lisa; Sozzani, Rosangela
Abstract: In contrast to animals, which complete organogenesis early in their development, plants continuously produce organs, and structures throughout their entire lifecycle. Plants achieve the continuous growth of organs through the initiation and maintenance of meristems that populate the plant body. Plants contain two apical meristems, one at the shoot and one root, to produce the lateral organs of the shoot and the cell files of the root, respectively. Additional meristems within the plant produce branches while others produce the cell types within the vasculature system. Throughout development, plants must balance producing organs and maintaining their meristems, which requires tightly controlled regulations. This review focuses on the various plant meristems, how cells within these meristems maintain their identity, and particularly the molecular players that regulate stem cell maintenance. In addition, we summarize cell types which share molecular features with meristems, but do not follow the same rules regarding maintenance, including pericycle and rachis founder cells. Together, these populations of cells contribute to the entire organogenesis of plants.